MENINGKATKAN HASIL BELAJAR IPS MELALUI PENGGUNAAN PEMBELAJARAN SNOWBALL THROWING KELAS VIII SMP NEGERI 2 KECAMATAN KELAYANG KABUPATEN INDRAGIRI HULU - CHARNELL CHRIESTYLL ANJLA (Jurusan Pendidikan Ilmu Pengetahuan Sosial Fakultas Keguruan dan Ilmu Pendidikan Universitas Riau, 2020)
The objectives of this research are: 1) To find out the implementation of teaching activities of teachers by using Snowball Throwing models for eighth grade students of SMPN 1 Kelayang, Indragiri Hulu Regency, 2) To find out the implementation of student activity learning using Snowball Throwing models for VIII grade students of SMPN 1 Kelayang Regency of Indragiri Hulu, 3) To find out the extent of the success of teaching and learning by using Snowball Throwing models in class VIII students of SMPN 1 Kelayang Regency of Indragiri Hulu. This research was conducted in 2 cycles. The subjects in this study were all students of class VIII1 of SMPN 1 Kelayang, Indragiri Hulu Regency, amounting to 33 people. The data analysis technique in this research uses descriptive quantitative. The results showed that student learning outcomes have increased with the average daily cycle repetition is 68.63% and increased on the daily cycle II replications by obtaining an average value of 72.87%. Then it can be concluded that by using the Snowball Throwing model can be the results of learning history subjects of eighth grade students of SMPN 1 Kelayang, Indragiri Hulu Regency.